Personality and Values dalam Pembelajaran Organisasi: Kajian Literatur Sistematis 2016–2025 - Clara Claudia; Vera Anatasya; Bunga Bunga; Mada Aditia Wardhana; Chonita Din (Lembag, 2025)
This study is a Systematic Literature Review (SLR) aimed at mapping the relationship between personality and values in the context of organizational behavior and learning. This topic has gained increasing relevance amid contemporary organizational challenges, such as cultural diversity in the workplace, ethical demands, and the need for individual integrity in decision-making. The review covers scholarly publications from 2016 to 2025 and adopts Schwartz’s Theory of Basic Human Values and the Big Five Personality Traits as its theoretical foundation. The findings reveal that the alignment between personal and organizational values positively influences team collaboration and learning effectiveness, while value dissonance significantly hampers knowledge dissemination. This review identifies four major research gaps: (1) limited integration between theory and human resource development (HRD) practices, (2) lack of cross-cultural and cross-sectoral studies, (3) insufficient longitudinal approaches, and (4) the absence of explicit frameworks linking personality and values to organizational learning systems. As recommendations, the study encourages the development of interactive models that incorporate the dynamics of values and personality, the expansion of cross-cultural research, and the implementation of longitudinal experiments. These efforts aim to formulate more adaptive human resource management strategies. The findings are expected to provide both theoretical and practical contributions to the development of organizational cultures aligned with individual values and personalities.